2018
DOI: 10.1039/c8nr06294c
|View full text |Cite
|
Sign up to set email alerts
|

Low-defectiveness exfoliation of MoS2 nanoparticles and their embedment in hybrid light-emitting polymer nanofibers

Abstract: MoS2 nanoparticles are obtained through a highly gentle exfoliation method and are embedded in polymer nanofibers to make them light-emitting.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…The frequency spacing between the two modes (at ∼30 cm −1 ) showed that the MoS 2 consisted of 7 to 12 layers. 43,44 Interestingly, it was observed that the intensity ratio of the two modes in each spectrum is ∼0.5, which confirmed that doping occurs in a homogenous manner in MoS 2 . 45,46 However, the absolute intensity decreased with subsequent doping with dopant atoms as the number of Mo−S bonds decreased, which again confirmed the change in the lattice constant upon doping.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…The frequency spacing between the two modes (at ∼30 cm −1 ) showed that the MoS 2 consisted of 7 to 12 layers. 43,44 Interestingly, it was observed that the intensity ratio of the two modes in each spectrum is ∼0.5, which confirmed that doping occurs in a homogenous manner in MoS 2 . 45,46 However, the absolute intensity decreased with subsequent doping with dopant atoms as the number of Mo−S bonds decreased, which again confirmed the change in the lattice constant upon doping.…”
Section: Resultsmentioning
confidence: 67%
“…Generally, the frequency difference of 18 cm –1 between the E 1 2g and A 1g modes suggested a multilayer signature. The frequency spacing between the two modes (at ∼30 cm –1 ) showed that the MoS 2 consisted of 7 to 12 layers. , Interestingly, it was observed that the intensity ratio of the two modes in each spectrum is ∼0.5, which confirmed that doping occurs in a homogenous manner in MoS 2 . , However, the absolute intensity decreased with subsequent doping with dopant atoms as the number of Mo–S bonds decreased, which again confirmed the change in the lattice constant upon doping . In addition, the shift in peak toward higher frequency supported the successful n-type doping in MoS 2 crystal lattice as evidenced by the Mott–Schottky analysis, which implied that the V and N atoms are located at the Mo and S substitutional sites, respectively, similar to the case of p/n type doping. , …”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…49 Upon doping with Zr, two absorptions band appeared at $557 and 613; peak at 557 nm can be attributed to nanosheets with lateral dimensions of a few tens of nm. 50 The peaks located at 613 nm signify-B direct excitonic-peak. 51 The above-stated results acquired from the analysis of MoS 2 nanosheets suggest quantum connement effect.…”
Section: Resultsmentioning
confidence: 99%